Deletion of PPARγ in Mesenchymal Lineage Cells Protects Against Aging-Induced Cortical Bone Loss in Mice. (15th February 2020) - Cao, Jay; Ding, Kehong; Pan, Guodong; Rosario, Raysa; Su, Yun; Bao, Yonggang; Zhou, Hongyan; Xu, Jianru; McGee Lawrence, Meghan E; Hamrick, Mark W; Isales, Carlos M; Shi, Xingming
Abstract: Bone loss in aging is linked with chronic low-grade inflammation and the accumulation of marrowfat in animals and humans. Peroxisome proliferator-activated receptor gamma (PPARγ), an adipogenic regulator, plays key roles in these biological processes. However, studies of the roles of PPARγ in age-related bone loss and inflammation are lacking. We hypothesized that deletion of PPARγ in bone marrow mesenchymal lineage cells would reduce bone loss with aging, potentially through a reduction in fat-generated inflammatory responses and an increase in osteoblastic activity. In the present study, we show that mice deficient of PPARγ in Dermo1-expressing mesenchymal lineage cells (Dermo1-Cre:PPARγ fl/fl ) have reduced fat mass and increased cortical bone thickness but that deficiency of PPARγ had limited effect on protection of trabecular bone with aging as demonstrated by dual-energy X-ray absorptiometry, µCT, and histomorphometric analyses. Conditional knockout of PPARγ reduced serum concentrations of adipokines, including adiponectin, resistin, and leptin, and reduced marrow stromal cell expression levels of inflammation-related genes. Inflammation genes involved in the interferon signaling pathway were reduced the most. These results demonstrate that disruption of the master adipogenic regulator, PPARγ, has a certain protective effect on aging-induced bone loss, suggesting that regulation of adipose function and modulation of interferon signaling are among the key mechanisms by which PPARγ regulates bone homeostasis during aging process.